2012
DOI: 10.1186/1753-6561-6-s2-s11
|View full text |Cite
|
Sign up to set email alerts
|

Linear models for breeding values prediction in haplotype-assisted selection - an analysis of QTL-MAS Workshop 2011 Data

Abstract: BackgroundThe aim of this study was to estimate haplotype effects and then to predict breeding values using linear models. The haplotype based analysis enables avoidance of loosing information due to linkage disequilibrium between single markers. There are also less explanatory variables in the linear model which makes the estimation more reliable.MethodsDifferent methods and criteria for marker and haplotype selection were considered. First, markers with MAF lower than 5% where excluded from the data set. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 5 publications
(5 reference statements)
1
9
0
Order By: Relevance
“…A similar finding was reported by Mucha and Wierzbicki [ 87 ] when random models considered haplotypes. These authors suggested that the inclusion of haplotypes as random effects in models may increase the precision in the estimation of breeding values of animals with unknown phenotype (whose breeding value has been inferred after the phenotypic observations from ancestors and/or descendants) while it prevents the use of high-dimensional models as compared to when models include SNPs.…”
Section: Discussionsupporting
confidence: 89%
“…A similar finding was reported by Mucha and Wierzbicki [ 87 ] when random models considered haplotypes. These authors suggested that the inclusion of haplotypes as random effects in models may increase the precision in the estimation of breeding values of animals with unknown phenotype (whose breeding value has been inferred after the phenotypic observations from ancestors and/or descendants) while it prevents the use of high-dimensional models as compared to when models include SNPs.…”
Section: Discussionsupporting
confidence: 89%
“…The GBLUP performances were more variable with a very low correlation given by the Mucha et al [ 17 ] version based on haplotypes, and higher values for the Zeng et al [ 10 ] and Ogutu et al [ 9 ] proposals. Finally, the fixed effect linear model was far below all other methods.…”
Section: Resultsmentioning
confidence: 99%
“…This was particularly true for the Bayes group, where the ranking BayesCπ > BayesB > BayesA > BayesZ > BayesS was preserved, and even more for the Ogutu et al [ 9 ] selection variable, with a very low correlation observed for the adaptative Elastic Net. Notably the random model proposed by Mucha et al [ 17 ] fell in the worst positions with this criterion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Boleckova et al ( 2012 ) drew a similar conclusion after having tested linear models with haplotypes as explanatory variables. A like tendency was described by Mucha and Wierzbicki ( 2012 ), who used simulated data in a haplotype-based breeding value prediction study. The correlations between EBV and DGV for production traits in the validation dataset were lower than the correlations presented by Solberg et al ( 2008 ).…”
Section: Discussionmentioning
confidence: 99%